Chemical composition and antibacterial activity of the essential oil of Ambrosia peruviana Willd. from Venezuelan plains - Yánez C., Carlos A. (2011)
In Venezuela, are currently exploring new sources of natural antibacterial agents, due to increased bacterial resistance, including essential oils derived from plants. For this reason in the present study we determined the chemical composition of essential oil obtained from leaves collected on Ambrosia peruviana Willd Guasdualito, Apure State, Venezuela. The volatile compounds were isolated by hydrodistillation in a Clevenger trap and then subjected to qualitative analysis and quantitative by gas chromatography-mass spectrometry (GC / MS) on an HP GC-MS System, model 5973, finding as the major compound gamma-curcumeno (23.99%) followed by curcumeno-ar (14.08%), bornyl acetate (10.35%), camphor (5.03%) and epoxide oximene (4.79%). The antibacterial activity of essential oil by the agar diffusion method with discs against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi and Pseudomonas aeruginosa showed activity against S. aureus, E. faecalis, E. coli and S. Typhi, with MIC values of 350-500 micrograms/ mL. This research represents the first report of antibacterial activity of A. peruviana.